ANALISIS PENGAKUAN PENDAPATAN PROYEK PEMBUATAN DERMAGA DI PALARAN PADA PT. TRISAKTI CIPTA NUSANTARA - Biasa, Diana - (EKONOMIA, 2019)
This study aims to determine the suitability between income analysis and use of revenue recognition methods at PT. Trisakti Cipta Nusantara based on PSAK Number 34, so it is necessary to analyze conditions which are the conditions of use of the method. By using the percentage completion method, the company must make an estimated percentage of jetty work that can be determined and accountable. Based on the results of the analysis and discussion the Company recognizes income based on physical progress completion without comparing the expenses incurred. Meanwhile, based on PSAK Number 34 by cost- to-cost method of revenue and expense recognition by paying attention to completion stage with cost incurred in reaching completion stage, so that income, expense and profit can be reported according to work proportional settlement.In this study the authors use a comparative analysis tool that compares the company's financial statements with financial statements according to Statement ofÂ  Accounting Standard (PSAK) Number 34 on Recognition of Construction Company Income. If the income recognition at PT. Trisakti Cipta Nusantara has not complied with Statement of Accounting Standard (PSAK) Number 34, because it has not compared the costs incurred to calculate the percentage of completion then the hypothesis is accepted but if the recognition of income at PT. Trisakti Cipta Nusantara is in conformity with Statement of Financial Accounting Standards (SFAS) no. 34 concerning the recognition of construction income and applying the method of calculating the percentage of settlement under PSAK Number 34 then the hypothesis is rejected.